Total phenolic content, flavonoid content and antioxidant potential of Petasites hybridus and related species from Croatia and considerations regarding their pharmaceutical significance - Friščić Maja; Vilić Katarina; Jurić Sandra; Pilepić Kroata Hazler; Maleš Željan (Acta Pharmaceutica)
Extracts obtained from common butterbur (Petasites hybridus), standardized to petasins, are existing pharmaceutical options for the treatment and/or prevention of allergic rhinitis (leaves) and migraine (rhizomes). In this study, the total phenolic content, flavonoid content, and antioxidant potential of ten samples of Croatian Petasites species (four P. hybridus, four P. albus, one P. kabli kianus, and one P. paradoxus) obtained by ultrasound-assisted extraction of leaves were compared. The total phenolic content (Folin-Ciocalteu assay) of methanolic leaf extracts ranged from 4.43 ± 0.09 to 10.76 ± 0.60 mg gallic acid equivalent g−1 dry mass (mg GAE g−1 DM) for P. hybridus and from 6.66 ± 0.43 to 19.92 ± 2.90 mg GAE g−1 DM for P. albus samples, while those of P. kablikianus and P. paradoxus were equal to 7.56 ± 0.17 mg GAE g−1 DM and 10.22 ± 0.46 mg GAE g−1 DM, respectively. Flavonoid content (AlCl3 assay) varied between 2.51 ± 0.10 and 4.03 ± 0.08 mg quercetin equivalent g−1 dry mass (mg QE g−1 DM) for P. hybridus and between 2.21 ± 0.09 and 5.22 ± 0.02 mg QE g−1 DM for P. albus samples, while those of P. kablikianus and P. paradoxus were equal to 5.59 ± 0.05 mg QE g−1 DM and 5.50 ± 0.09 mg QE g−1 DM, respectively. Antioxidant potential was in high correlation with total phenolic content (r = 0.93, p < 0.001). Due to the expected contribution of plant polyphenols and flavonoids to the activity of butterbur extracts and their observed great variabilities, determining the content of these compounds may be of interest to the pharmaceutical industry.